2021
DOI: 10.1080/09593985.2021.1911011
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ views on their role in self-management approaches: A qualitative systematic review

Abstract: Self-management has been an increasingly important aspect of helping people manage their long-term conditions. The aim of this qualitative review was to synthesise the views of physiotherapists concerning their delivery of a self-management approach. A systematic search was conducted on six electronic bibliographic databases to identify relevant primary studies.Studies were assessed for quality and data extracted. Qualitative data were analysed using thematic synthesis. A total of 1189 studies were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…These findings are supported by a study by Doerfler and Kulnik (66) that found that a trusting client-therapist relationship entails showing commitment, shared decision-making and 'to make an effort to get to know the person' (p. 3631) (66). The systematic review by Killingback et al (10) found that when using a self-management approach, physiotherapists liked to be seen as the expert with a desire to be in control. They also found that physiotherapists saw a "high-quality patient-therapist relationship" (p. 8) (10) characterized as being able to listen to patients and having good communication skills as central to working together with patients in a self-management approach (10).…”
Section: Therapists' Expertisementioning
confidence: 78%
See 2 more Smart Citations
“…These findings are supported by a study by Doerfler and Kulnik (66) that found that a trusting client-therapist relationship entails showing commitment, shared decision-making and 'to make an effort to get to know the person' (p. 3631) (66). The systematic review by Killingback et al (10) found that when using a self-management approach, physiotherapists liked to be seen as the expert with a desire to be in control. They also found that physiotherapists saw a "high-quality patient-therapist relationship" (p. 8) (10) characterized as being able to listen to patients and having good communication skills as central to working together with patients in a self-management approach (10).…”
Section: Therapists' Expertisementioning
confidence: 78%
“…The systematic review by Killingback et al (10) found that when using a self-management approach, physiotherapists liked to be seen as the expert with a desire to be in control. They also found that physiotherapists saw a "high-quality patient-therapist relationship" (p. 8) (10) characterized as being able to listen to patients and having good communication skills as central to working together with patients in a self-management approach (10). The current study did not find that the therapists had a desire to be in control -but rather perceived themselves to have a coaching role, ready to give advice and share expertise when it was requested by the stroke survivors.…”
Section: Therapists' Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the change from service users being passive recipients to becoming an active participant with a voice. In rehabilitation this presents a cultural change in service user and physiotherapist roles [38][39][40][41][42]. Being mindful of this shift in culture and setting expectations at the beginning of a consultation would enhance the understanding of both parties as they navigate the roles they can play in enabling self-management of long-term health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite encouragement to engage in healthy conversations (Bancroft and Moss, 2016;National Health Service, 2016) no consensus has been reported on how physiotherapists promote healthy lifestyles (Killingback et al, 2022;Shore and Hebron, 2020). Approaches used by physiotherapists to deliver advice have been shown to be inconsistent, conflicting and have not addressed long-term health promotion (Lowe, Littlewood, and McLean, 2018;Osborn-Jenkins and Roberts, 2021).…”
Section: Introductionmentioning
confidence: 99%